Penerapan Strategi Problem Based Learning dengan Wawasan Kristen Alkitabiah untuk Memotivasi Keaktifan Siswa - Fery Mallappa; Kurniawati Martha (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
Student activeness is one of the main factors determining the success of learning. The learning strategy used by the teacher will greatly determine student activity in class. Mistakes in choosing a learning strategy will make students passive in class. The passive attitude of students will make them unable to learn optimally. Therefore, it is important for teachers to design learning that can facilitate students being actively involved in every learning process. Not only that, it is important for every Christian educator to design active and meaningful learning so that students also get the opportunity to admire God in the learning process. The strategy taken is the Problem Based Learning strategy with Biblical Christian insights because the main goal is not only for students to be active but also for students to admire God more through the concepts learned in class. The purpose of this study is to describe the application of Problem Based Learning strategy with Biblical Christian insights in order to motivate student activeness. The method used in this research is descriptive qualitative method. The research was conducted in one of the Christian schools in Tangerang which was lasted for one month. The results showed that the application of Problem Based Learning strategies with Biblical Christian insights was carried out through five stages, namely orienting, organizing, assisting problem investigation, developing and presenting student work, analyzing and evaluating the problem-solving process, which successfully motivated student activeness in learning with the topic of expansion.